Pengaruh Beban Kerja dan Work Life Balance Terhadap Produktivitas Kerja Pegawai pada Dinas Pendidikan dan Kebudayaan Kabupaten Tasikmalaya - Silpa Fauziah; Arga Sutrisna; Nita Fauziah Oktaviani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study was to determine the effect of Workload and Work Life Balance on Employee Work Productivity at the Tasikmalaya Education and Culture Office. The method used in this study is causality, with a research sample of 64 respondents who are structural employees of the Tasikmalaya Education and Culture Office, by using primary data. The analysis tool used in this study was multiple linear regression using SPSS version 25. Based on the results of the study, it can be seen that Workload and Work Life Balance simultaneously have a significant effect on the Work Productivity of Employees of the Tasikmalaya Regency Education and Culture Office. The workload partially does not have a significant effect on the work productivity of employees of the Education and Culture Office of Tasikmalaya Regency and Culture Office Employees and Work Life Balance partially has a significant effect on the Work Productivity of Tasikmalaya Regency Education and Culture Office Employees.